A new genre of fluorescence recovery assay to evaluate polo-like kinase 1 ATP-competitive inhibitors. Issue 36 (3rd September 2020) - Tsuji, Kohei; Hymel, David; Burke, Terrence R.
Abstract : Using a probe consisting of a fluorescein-labeled variant of the potent polo-like kinase 1 (Plk1) inhibitor BI2536, we determined the IC50 of ATP-competitive Type 1 inhibitors of Plk1 by means of a fluorescence recovery assay. Abstract : Using a probe consisting of a fluorescein-labeled variant of the potent polo-like kinase 1 (Plk1) inhibitor BI2536 [FITC-PEG-Lys(BI2536) 4 ], we were able to determine half maximal inhibitory concentration (IC50 ) of ATP-competitive Type 1 inhibitors of Plk1 by means of a fluorescence recovery assay. This methodology represents a cost-effective and simple alternative to traditional kinase assays for initial screening of potential Plk1 inhibitors.